Remove the parentheses around the expression 1
Um.. Both of those equations are the exact same. Divide both sides of the first equation by 6. You get:
![\frac{30x - 42y}{6} = \frac{-6}{6} \\ 5x - 7y = -1](https://tex.z-dn.net/?f=%20%5Cfrac%7B30x%20%20-%2042y%7D%7B6%7D%20%3D%20%5Cfrac%7B-6%7D%7B6%7D%20%5C%5C%205x%20-%207y%20%3D%20-1%20)
That is the exact same as the second equation. This system has an infinite number of solutions. 5x - 7y = -1 is a line, so basically every point on that line is a solution to the system.
For example,
![x = 0](https://tex.z-dn.net/?f=%20x%20%3D%200%20)
and
![y = \frac{1}{7}](https://tex.z-dn.net/?f=%20y%20%3D%20%5Cfrac%7B1%7D%7B7%7D%20)
would work, but so would
![x = 1](https://tex.z-dn.net/?f=%20x%20%3D%201%20)
and
Answer:
cant see i am dumb
Step-by-step explanation:
and blind i cant see at all my gide dog wrote dis woof woof
Answer:
a. $3.36
b. $70.86
Step-by-step explanation:
5% of $67.50 is $3.36
$67.50 + $3.36 = $70.86